Framing international media in the face of social movements: CNN and Al-Jazeera English in the fall of Morsi (Communication & Society, 2016)
This research paper aims to analyse and compare the role of two of the major television networks in international news coverage, Al-Jazeera English and CNN, in relation to one of the most important social movements of the last decade known as the Arab Spring. The study specifically focuses on Egypt during the coup of July 2013, when President-elect Mohamed Morsi was overthrown by the army after weeks of protests. Through a qualitative content analysis based on the framing theory, we will look at the position of both channels regarding a coup emerging from popular uprisings and identify the differences between the two channels. The results show frames matching the definition of conflict (crisis and coup), military power and the legitimacy of democracy. As for divergences, it highlights CNN’s stance towards the coup as a necessary evil, while Al-Jazeera English takes a more Islamist approach and prefers to emphasize its democratic legitimacy. The transition to democracy in Egypt is not seen as a linear process of uninterrupted progress, but events such as the coup are seen as slight setbacks in the development of the conflict. These setbacks are a result of the dynamics of power in Egypt, where the military remain in charge above and beyond social movements